2012
DOI: 10.1007/s11239-012-0857-9
|View full text |Cite
|
Sign up to set email alerts
|

Dabigatran attenuates thrombin generation to a lesser extent than warfarin: could this explain their differential effects on intracranial hemorrhage and myocardial infarction?

Abstract: Compared with warfarin, dabigatran is associated with less intracranial hemorrhage, but an increased risk of myocardial infarction. To explore these phenomena, we compared their effects on thrombin generation. Thrombin generation in plasma from 10 patients taking therapeutic doses of warfarin (mean INR 2.6) was compared with that in plasma containing 250 ng/mL dabigatran. Although lag times were similar when thrombin generation was induced by recalcification or with a range of tissue factor concentrations, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 15 publications
4
37
0
3
Order By: Relevance
“…One postulated mechanism is that warfarin is associated with greater thrombin suppression in the brain and pathological thrombosis at sites of atherosclerotic plaque disruption. 41 This might support the selection of a TSOACs compared with VKAs in patients considered to be at high risk of intracranial bleeding who require anticoagulant treatment.…”
Section: Discussionmentioning
confidence: 86%
“…One postulated mechanism is that warfarin is associated with greater thrombin suppression in the brain and pathological thrombosis at sites of atherosclerotic plaque disruption. 41 This might support the selection of a TSOACs compared with VKAs in patients considered to be at high risk of intracranial bleeding who require anticoagulant treatment.…”
Section: Discussionmentioning
confidence: 86%
“…In contrast, although the DOACs also prolong the time to initiation of thrombin generation, they have only modest effects on the thrombin burst because their activity is limited to stoichiometric inhibition of factor Xa or thrombin. 101 With minimal effects on the thrombin burst, the DOACs may enable the generation of sufficient concentrations of thrombin to stabilize the fibrin network such that it prevents leakage of blood from the intravascular space. Additional work is needed to validate these concepts.…”
Section: Intracranial Bleedingmentioning
confidence: 99%
“…Given the wide interindividual variation in plasma concentrations, the net biochemical effect may also be variable. In an attempt to document this effect, Dale et al showed that at therapeutic INR levels, warfarin provided greater suppression of thrombin generation indices as compared to dabigatran, although this study was quite small [29]. A recent study shows that in 'real-life' patients, there is a wide range of dabigatran concentrations, but it also indicates that patients that have an initial high concentration tend to remain high on repeated testing [30].…”
Section: Dabigatran Etexilatementioning
confidence: 89%